Health and nutrition: emerging and reemerging issues in developing countries - Flores, Rafael; Gillespie, Stuart (International Food Policy Research Institute, 2001)
A healthy and nutritionally well-fed population is indispensable for economic growth and development. Health and nutritional status affect the capacity to learn, which in turn determines productivity and economic growth. Evidence from developing countries shows that adult productivity depends to a considerable extent on the contribution health and nutrition during early childhood make to educational attainment. Studies also show that a healthy adult with a nutritionally adequate diet has a higher level of economic productivity in both own-farm production and the labor market than one who eats and keeps less well.